Influence of Process Temperature on Drying Kinetics, Physicochemical Properties and Antioxidant Capacity of the Olive-Waste Cake - Zamorano-Riquelme, M (2014)
The objective of this study was to determine the effect of drying temperature on the drying kinetics, proximal analysis, energy consumption and the antioxidant capacity of the olive-waste cake "Picual" variety from 40 to 90 C. Evaluation of proximal analysis evidenced the influence of temperature on the waste parameters. Values of effective moisture coefficients were in the range of 1.97-6.05 × 10-9 m2 s -1 under the studied conditions. Activation energy was found to be 28.24 kJ mol-1. The Weibull model was successfully applied (r 2 > 0.973). Specific energy consumption decreased as temperature increased, showing the effect of drying times over temperature. Although dehydrated samples decreased the initial total phenolic content, significant differences were not detected. Effects of drying temperatures did not present significant differences on antioxidant capacity (ORAC and DPPH) when compared to fresh samples. The oleic acid (main fatty acid in fresh samples) presented a maximum increased at 90 C. © 2013 Elsevier Ltd. All rights reserved.